Media Pengenalan Peti Kemas Logistik Menggunakan Augmented Reality Berbasis Android - Vio Kartiko; Puteri Noraisya Primandari (Jurnal Teknologi Informasi dan Multimedia, 2023)
Containers are the most important part in the world of logistics, where the container is a medium for sending cargo or goods from the sender to the recipient. A container is a square-shaped box that is specially carved with a certain size made of iron or aluminum with a door on one side, the box has an important role in the export and import of goods. The study developed the Augmented Reality app using the Markerless and Markerbased methods to visualize Android-based 3D Logistics Box objects. The method used in this application development is the Software Development Life Cycle model Waterfall. Logistic container identification materials that will be used as 3D objects on applications are: dry container, isotank container, open top container, open side container, reefer container and flatrack container. The result of the development of this app is a container recognition media that runs on the Android smartphone using Augmented Reality technology. Based on the results of functionality testing / blackbox testing, it can be concluded that the application runs according to its function and the input/output process successfully produces a valid output. The marker accuracy test obtained a total percentage level of precision of 66.6%, and the markerless accurate test obtains a total level of accuration of 100%. Usability testing by conducting a questionnaire on 30 respondents could conclude all aspects of usability, functionality, efficiency and portability obtain a percentage score of Likert’s scale of 91%.